(untitled) (Research, Society and Development, 2020)
The new coronavirus appeared in China at the end of 2019 and already in March 2020 it was considered a pandemic infecting millions of people with its high transmissibility power. Because of this, the health of many people who are more fragile due to pre-existing conditions may also be more susceptible to greater consequences. The purpose of this study is to gather other research that describes which people are most subject to COVID-19 and their complications in their lives. The present study is based on the norms of a bibliographic review and was carried out through searches in the electronic databases: Web of Science and ScienceDirect, using the keywords in English and Portuguese. Of the 1994 results found, only 17 met the inclusion and exclusion criteria. The results found conceived the answer to the objective, describing the situation of individual vulnerability through the classification of a group of risks containing people of high age, general cardiovascular complications, diabetes, hypertension, renal dysfunction, liver problems, patients with some type of cancer , postoperative, obesity and momentarily fragile people who deserve a little more attention as pregnant women, newborns and children. Thus, it is concluded that people who fall into one or more of these categories deserve extra care and support both to address their inherent weaknesses and to overcome the pandemic caused by SARS-Cov-2.